Development Steps of Avionics and Flight Control System of Flight Vehicle - Herma Yudhi Irwanto; Purnomo Yusgiantoro; Zainal Abidin Sahabuddin; Romie Oktovianus Bura; Aris Sarjito; Oka Sudiana; Faisa Lailiyul Mutho' Affifah (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2023)
The success of a research is highly dependent on the method adopted, especially research related to dangerous and expensive matters which will certainly require special handling in the development or maintenance steps. One of them is research related to space technology such as aviation and rocketry technology, which is very dependent on the design model of the flying vehicle and, in general, will always use simulation to ensure that the entire system being built is carried out safely and can be implemented properly according to plan. In the development of the prototype flying vehicle, especially the development of the avionics and flight control system, the vehicle will go through sequential simulation steps from Software in the Loop Simulation (SILS), Hardware in the Loop Simulation (HILS), and Ready-to-Fly System (RTFS). In this paper, the simulation steps will be described with the intention of facilitating integration and testing of each sub-system being developed, testing the control strategy applied or eliminating bugs if something goes wrong. In the end, with a series of flying vehicle simulations, it can be developed quickly and cost-effectively, including saving human resources.